Peran UMKM sebagai Motor Penggerak Lapangan Kerja di Desa Sendang Kecamatan Wonogiri untuk Mendukung Sustainable Development Goals - Sugiyanto Sugiyanto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
This article attempts to explore the role of Micro, Small and Medium Enterprises (MSMEs) as a driving force for employment in Sendang Village, Wonogiri District to support Sustainable Development Goals (SDGs). This research uses a descriptive qualitative approach. Data was obtained through interviews, observation and collecting related documents. Social entrepreneurship theory is used to analyze the data in this research. Novelty in this research is the theory used to analyze and the existence of SDGs elements in studying the role of MSMEs as a driving force for employment. The research results show that MSMEs in Sendang Village help create jobs because the presence of MSMEs requires labor. Some of the MSMEs that are developing in Sendang Village are fish processing into floss and nuget, patchwork processing, shoe production, dry tempe production, food stalls and souvenir shops, fish cultivation. The presence of MSMEs plays an important role in Sendang Village. Many MSMEs in Sendang can absorb labor both from within Sendang Village and from outside the village. The Sendang Village Government has provided support with various efforts, including improving the quality of human resources and supporting equipment. The success of some MSMEs in Sendang Village depends on the large number of tourists who come to various tourist attractions in the village. Considering the large number of MSMEs that operate because of the support of natural tourism potential in the Sendang area. The challenges faced by some MSMEs in Sendang Village, especially those who are involved in the restaurant business. Stall owners are subject to restaurant tax of 10% of turnover, not net profit. In fact, the tax is already in effect in all regions and is imposed on buyers. However, in Wonogiri, if it is implemented, it will not be fully accepted by buyers. Another obstacle is that business owners who have employees must include them as BPJS participants. In fact, some MSME players who are just starting a business are considered something burdensome.